Changing the essence : the art of creating and leading fundamental change in organizations - Beckhard, Richard (Jossey-Bass Pub. San FranciscoUS, 1992)
Advocates adopting a learning mode that values learning and improvement equally. Provides a profile of a learning oeganization and discusses the key factors in leading a value-driven effort. Examines five themes which may serve as the focus of fundamental change, and the management process of choosing and prioritising themes. Presents the change leader as a participant in charge, and examines the personal dilemmas he faces. Identifies and explains steps to be taken during the transitional phase.\n \n